PENGARUH USIA, PENGALAMAN, DAN PENDIDIKAN DEWAN KOMISARIS TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Real Estate dan Property yang Go Public Tahun 2010-2012 di Bursa Efek Indonesia) - Shelly Tri Maulia; Indira Januarti (Diponegoro Journal of Accounting, 2014)
This study aims to analyze and provide empirical evidence about the effectof age, tenure and education of board commissioners on financial statement quality. Several previous studies showed varying results. To obtain valid results, then doing a test on each variable based on the hypothesis constructed.The  samples  used  were  selected  by  purposive  sampling  method.  A population was 42 real estate and property companies listed in Indonesia Stock Exchange. After   reduced   with   some   criteria,   20   companies   identified   as   samples. Observation period was 2010 to 2012, so the total number of sample used was 60 samples. Multiple regressions were used to examine the hypothesis.The results indicate that age and board of Commissioners education, are significantly effect positive the financial statement quality. On the other side, board of Commissioners experience has no effect positive on the financial statement quality.